Some legal consequences of transforming an employment relationship into a fictitious – not an employee – legal relationship: abstraction or effective practice? - Świątkowski, Andrzej Marian (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The author compares criminal law norms (Article 218 of the Criminal Code) with the provisions of labor law (Articles 2 and 22 of the Labor Code) introduced and used by the legislator to prevent the use of fictitious forms of employment. Primacy should be given to the provisions of the latter branch of law. The legal and criminal norms protect only the signs of an employee misconduct, and not the employees fictitiously positioned by employing persons and entities as persons employed on the basis of and under civil law contracts. We are dealing not with effective practice but with abstraction. He believes that the principles formulated in the aforementioned provisions of the Code of Civil Procedure are not automatically and effectively implemented.